Menelusuri aktivitas generasi bangsa: studi femenologis eksplorasi pengalaman gerak yang bermakna pada peserta festival olahraga pendidikan - Fitriasari, Rika Aninggar; Septiana, Eva (Jurnal Pendidikan Jasmani Indonesia, 2025)
This study investigates the meaningful movement experiences of students involved in the Festival of Educational Sports, concentrating on their physical, emotional, cognitive, and social development. Utilizing qualitative research with a phenomenological approach, the study seeks to comprehend the significance of engaging in physical activities both within school settings and outside of them, particularly in relation to the educational sports festival. The findings indicate that school-based activities, such as physical education classes and extracurricular sports, provide a formal environment for students to cultivate healthy habits, although their motivation to participate may differ. In contrast, sports activities outside of school are shaped by social influences, personal motivations, and the availability of facilities, with participation in sports clubs and community events offering avenues for personal growth and enjoyment. The Festival of Educational Sports, as explored in this research, presents an inclusive and enjoyable platform for students to enhance teamwork, social skills, and emotional intelligence. Participation in the festival encourages collaboration, self-expression, and the enjoyment of physical movement, contributing to the establishment of lifelong active habits and a healthy lifestyle. This study underscores the importance of creating engaging and meaningful sports experiences for young individuals, fostering their ongoing involvement in physical activity throughout their lives.